AZEuS: an adaptive zone Eulerian scheme for computational magnetohydrodynamics - Ramsey, Jonathan P.; Clarke, David; Men’shchikov, Alexander (The astrophysical journal. Supplement series, 2012)
A new adaptive mesh refinement (AMR) version of the ZEUS-3D astrophysical magnetohydrodynamical fluid code, AZEuS , is described. The AMR module in AZEuS has been completely adapted to the staggered mesh that characterizes the ZEUS family of codes on which scalar quantities are zone-centered and vector components are face-centered. In addition, for applications using static grids, it is necessary to use higher-order interpolations for prolongation to minimize the errors caused by waves crossing from a grid of one resolution to another. Finally, solutions to test problems in one, two, and three dimensions in both Cartesian and spherical coordinates are presented.